THE ROLE OF METAPHORS IN THE CLASSIC ENGLISH LITERATURE - Альмуханова, Ж.Т.; Ильченко, К.А. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
From the earliest times metaphor plays a significant role in the reflection of objective reality. In spite of the fact that the phenomenon of metaphor represents enormous scientific interest, the use of metaphor is not limited to only scientific literature. Our everyday speech is also full of metaphors Different notions of me-taphor were defined in this article, also functions and classifications of metaphor according to the points of view of different authors were identified. The period of classic English literature was chosen for our research.
Keywords: metaphor; role; function; classification; literary work